2006
DOI: 10.1089/ten.2006.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Wnt Signaling Promotes Proliferation and Suppresses Osteogenic Differentiation in Human Adipose Derived Stromal Cells

Abstract: Multipotential adult mesenchymal stem cells (MSC) are able to differentiate along several known lineages, and lineage commitment is tightly regulated through specific cellular mediators and interactions. Human adipose tissues contain cell populations that have similar characteristics to bone marrow stromal cells. Wnt proteins have been reported to be involved in proliferation and differentiation of stem cells. RNA interference (RNAi) has recently emerged as a specific and efficient method to silence gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 34 publications
7
57
2
Order By: Relevance
“…Our observation that Wnt3a treatment inhibits osteogenic differentiation in mesenchymal cells (e.g., ASCs and E16) is consistent with previous in vitro studies performed on other multipotent mesenchymal cells. [41][42][43][44] In addition, our study provides also in vivo evidence complementing in vitro results. It must be pointed out that in vitro Wnt3a treatment represents a constant and continuous treatment of cells, compared to in vivo treatment where calvarial bones are initially exposed to doses of Wnt3a protein, which gradually decreased overtime.…”
Section: Discussionsupporting
confidence: 71%
“…Our observation that Wnt3a treatment inhibits osteogenic differentiation in mesenchymal cells (e.g., ASCs and E16) is consistent with previous in vitro studies performed on other multipotent mesenchymal cells. [41][42][43][44] In addition, our study provides also in vivo evidence complementing in vitro results. It must be pointed out that in vitro Wnt3a treatment represents a constant and continuous treatment of cells, compared to in vivo treatment where calvarial bones are initially exposed to doses of Wnt3a protein, which gradually decreased overtime.…”
Section: Discussionsupporting
confidence: 71%
“…Elucidating how Wnts act as instructive cues for the recruitment, maintenance, and maturation of MSCs and their differentiated progenies is of primary interest given the potential use of these cells in regenerative medicine. Prior studies have implicated canonical Wnt signaling in the regulation of bone metabolism at several levels, in amplifying the undifferentiated MSC pool, (7,8) commitment of undifferentiated MSCs to the osteoblast lineage, (13,14) and stimulation of their differentiation. (14) However, differences in cell preparations, use of models that did not take into account the cellular context, or use of nonphysiologic loss-and gain-of-function approaches are some of the reasons for the emergence of contrasting data.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) Moreover, the overexpression of LRP5, a key coreceptor specifically involved in canonical Wnt signaling, was reported to increase proliferation of MSCs. (9) Activation of Wnt signaling by lithium chloride, a nonspecific GSK-3 inhibitor, was shown to suppress dexamethasone-induced osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that activation of Wnt signaling in hMSCs inhibits osteogenic differentiation [34][35][36][37], and the high number of Wnt-regulated genes in 8-br-cAMP possibly negatively correlates with osteogenic differentiation. Insulin-like growth factor (IGF) signaling and in particular the IGF binding proteins (IGFBPs), were also differentially expressed between the two types of cultures.…”
Section: -Br-camp Induces Adipogenic Gene Expressionmentioning
confidence: 81%